News as a Learning Material for Teaching Basic Grammar to Improve Students’ English Proficiency - Ariij Diandra Taqiyyah; Aswir Aswir (Scripta : English Department Journal, 2022)
Understanding English news is one of secondary students’ competency in English skills. The researchers choose Arirang News as a learning material for teaching grammar. The purpose of this study was to find out whether or not Arirang News effective to be implemented as a learning material in order to improve students’ English proficiency for ten graders of high school students. The research method was a quantitative method with pre-experimental design. The researcher took X BDP B consist of 33 students as experimental class. The result showed that Arirang News can be said to be effective because based on data post-test experiments were higher than the results of the data pre-test.